AKHLAK PENDIDIK DAN PESERTA DIDIK (PRESPEKTIF KH. M. HASYIM ASY’ARI DAN PROF. DR. Hj. ZAKIYAH DARADJAT) - Rusdiyanto, Ali; Hijriyati, Muthi’ah; Arini, Aida (Education, Learning, and Islamic Journal, 2020)
National education begins which to put aside the moral values that the authors include as the background of this study, it can be seen from the number of educators and students who experience a decline or even do not have the value of politeness. Indeed, the formation of morals or character is the main goal in Islamic education which can form a moral, pure, and clean soul and able to distinguish between truth and fault. The author's interest is to study how KH. M. Hasyim Asy'ari and Prof. Dr. Hj. Zakiyah Daradjat suggests a moral education that can solve the problem of moral depravity that occurs in this country. The aims of this research are 1. To find out how moral education focuses on the morals of educators and students Perspective KH. M. Hasyim Asy'ari and Prof. Dr. Hj. Zakiyah Daradjat, 2. To find out the similarities and differences in the morals of educators and students from the perspective of KH. M. Hasyim Asy'ari and Prof. Dr. Hj. Zakiyah Daradjat. The library research is used in this writing. Research with literature reading as the basis for data collection was carried out carefully so that the information was relevant to the research topic or study topic. Also in this research approach is a qualitative approach, with content analysis methods to analyze its content as well as scientific analysis of thought. The context in this study and focuses on education which focuses on morals by Kyai Hasyim Asy'ari and Prof. Dr. Hj. Zakiyah Daradjat. The research shows 1. Education that focuses on the moral perspective of KH. M. Hasyim Asy'ari includes 2 aspects, namely: 1) Educators include a. educators who must have morals b. how to become a professional educator and his efforts c. an educator's strategy in teaching 2) Learners include a. students who prioritize morals b. efforts to become students with good morals c. strategies and procedures for students in learning. 2. Prof. perspective moral education. Dr. Hj. Zakiyah Daradjat where 3 factors are the main basis, namely: a. factor figure b. texture factor c. cultural factors 3. The similarity of moral education offered by Hasyim and Mrs. Zakiyah, namely in terms of educational materials, which are both always reminded to get closer to Allah SWT, moral education (interaction between educators and students), and social relations basic namely the community. 4. There are also differences in the formation of KH M. Hasyim Asy'ari who is more inclined towards the educational environment because KH. M. Hasyim Asy'ari is in the pesantren environment, Prof. Dr. Hj. Zakiyah Daradjat is located in a family environment.